(untitled) (Research, Society and Development, 2022)
Objective: This is a qualitative study, whose objective was to investigate the scientific literature on plant species potentially active against Plasmodium sp. Method: This is a systematic literature review, which aimed to analyze the most recent articles published between the years 2005-2020 in the languages: English and Portuguese. The studies were chosen in an integrative way from the following databases: PubMed (National Library of Medicine), LILACS (Latin American and Caribbean Health Sciences Literature), Science Direct (Explore, scientific and medical) and SciELO (Scientific Electronic Library Online). Results and discussion: 115 species distributed in 50 botanical families were found in antiplasmodial inhibition studies, of which 66 different types of extracts showed action in eliminating these parasites, while 59 of these extracts were inactive. Of this total number, the most studied species belong to the Asteraceae and Fabaceae families. In addition, another 141 botanical species were cited in ethnobotanical surveys in different regions of the world. Aponynaceae and Lamiaceae were the most representative plant families among the studies focused on this topic. The data also allowed us to understand how popular knowledge can help to establish scientific discoveries about plants with antimalarial potential. In addition, environmental conditions were identified as determining factors for the production of chemical constituents in these plants. Conclusion: Efforts to identify plants with active potential in combating the parasite have increased significantly in recent years; however, it is important to emphasize that the preservation of biodiversity needs to be an important aspect of ethnobotanical research in order to guarantee the sustainable use of available resources.